PROFESI SEBAGAI TAREKAT - Munji, Ahmad (TEOLOGIA, 2015)
Abstract: Generally in the teachings of any religion, both divine religions such as Islam, Christianity and Judaism, or earth religions such as Hinduism, Buddhism there is a polarization between religion and economic activity. So that all activities which seeking riches is viewed negatively and not in accordance with the lofty ideals of spirituality. In the teachings of Islamic religion there is also tendency that sees economic activity as an activity that is in appropriate for a religious. By using content analysis, the studies illustrate that everyone can make his profession as a path to God. Provided that each profession held by Islamic guidance, according to the Quran and the Hadith. Abstrak: Dalam ajaran keagamaan secara umum, baik agama-agama samawi seperti Islam, Kristen dan Yahudi, maupun agama bumi seperti Hindu, Buddha dan lain sebagainya terdapat anti-nomi antara agama dan kegiatan ekonomi. Sehingga seluruh kegiatan yang mencari kekayaan dipandang negatif dan tidak sesuai dengan cita-cita luhur spiritualitas. Dalam ajaran Agama Islam juga terdapat tendensi yang cukup kuat yang memandang kegiatan ekonomi sebagai aktifitas yang tidak pantas bagi manusia yang taat beragama. Dengan menggunakan analisis isi (content analysis), setudi ini menggambarkan bahwa, setiap orang bisa menjadikan profesinya sebagi jalan menuju kepada Allah. Asalkan setiap apa yang menjadi aktifitas keseharianya dilaksanakan berdasarkan tuntunan Islam, sesuai dengan al-Qurâan dan hadis Nabi Muhammad. Keywords: profesi, wirid, al-Quran, hadis, tarekat.